Usage of the visual elements in the interior designing of indoor swimming pools (Al-Academy, 2023)
The research specializes in (Usage of the visual elements in the interior designing of indoor swimming pools), the research seeks to provide a study that contributes to providing scientific and knowledge material, as a reference for researchers, students of interior design and architecture, and companies constructing indoor swimming pools.The objective research is to detect the actual state of the interior design of the indoor swimming pools, and recognize the most important standards and techniques used in its design to provide appropriate design solutions if needed also Proposing a development proposals for the interior design of indoor swimming pools, the theoretical framework of this study, included two sections, The first one talked about the emergence of indoor swimming pools and their components, and the second section talked about the visual elements in the interior design of the indoor swimming pools, as the descriptive approach was followed in the process of analyzing the research sample, so the most important result was: (The research sample did not achieve all of the standards required to be available in the proses of designing its visual elements, it did accomplish some of them), and the most important conclusion was: (international design standards must be followed in the processes of designing the visual elements (colors, lighting and finishing materials) of indoor swimming pools, because these elements are directly related to ensuring the comfort and safety of their users)